Rancang Bangun Aplikasi Analisis Kebutuhan Pelatihan Berbasis Kompetensi Pada PT.SMART Tbk. - Firmansyah, Ayif; Supriyanto, Antok; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
As a manufacturer of cooking oil, margarine and oil with raw material of palm oil, PT. SMART Tbk. formed a refinery business unit to manage, market and sales the products. The refinery business unit PT. SMART Tbk. Surabaya hires employees who are required to have knowledge and skills according to the type of work. Therefore, the company held training each year aims to develop the knowledge and skills of employees optimally.According to the results of employee’s competency assessment on Production Department about implementing Hazard Analysis Critical Control Point in 2012 conclude that the employee’s competency has not been as expected. To overcome that problem, required to design and build an application of training need analysis based competency. The analytical method to be used is the gap analysis between competencies required by the position with competencies owned by employee.Based on the result of testing and evaluation, it’s known that the application can determine the type of training effectively to what is actually needed by employee in accordance with requirement of competence on the job. In addition, using the application will also affect the cost savings because not at all employees are given training that is not required.